The Administration of Islamic Study Curriculum by School Administrators Under the Offices of Primary Education Service Area In Narathiwat Province - เล็งฮะ อับดุลซอมัด; พ่วงสมจิตร์ ชูชาติ; อุทุมพร นงเยาว์ (Al-HIKMAH Journal, 2018)
This research was a mixed-method research with the following purposes: (1) to study the level of administration of Islamic Study Curriculum by school administrators under the Offices of Primary Education Service Area in Narathiwat province; (2) to compare the levels of administration of Islamic Study Curriculum by school administrators as perceived by Islamic Study teachers classified by general education qualification, Islamic Study qualification, teaching experience, and the supervising Office of Narathiwat Primary Education Service Area; and (3) to study the problems, needs, and guidelines for administration of Islamic Study Curriculum by school administrators under the Offices of Primary Education Service Area in Narathiwat province. The research sample in the quantitative study consisted of 214 Islamic Study teachers under the three Offices of Primary Education Service Area in Narathiwat province, obtained by stratified random sampling; while the research sample of informants for the qualitative study consisted of 15 school administrators, supervisors, and heads of academic affairs of school, all of which were purposively selected from schools in the three Narathiwat primary education service areas that were offering instruction in the Islamic Study Curriculum. The employed research instrument for the quantitative study was a 5-scale rating questionnaire with reliability coefficient of 0.98; while the research instrument for the qualitative study was a semi-structured interview form. The quantitative study data were statistically analyzed using the percentage, mean, standard deviation, and one-way analysis of variance; while the qualitative study data were analyzed by interpretation in order to derive at inductive conclusion. Research findings were as follows: (1) the overall administration of Islamic Study Curriculum by school administrators under the Offices of Primary Education Service Area in Narathiwat province was rated at the high level; (2) Islamic Study teachers who were different in general education qualifications, Islamic Study qualifications, teaching experiences, and the supervising offices under which they worked did not significantly differ in their perceptions of administration of Islamic Study Curriculum by school administrators; and (3) regarding the problems, needs, and guidelines for administration of Islamic Study Curriculum by school administrators under the Offices of Primary Education Service Area in Narathiwat province, it was found that the most urgent need was to solve the budget problems, with the proposal for the concerned work agencies to allocate sufficient budget for Islamic Study Curriculum administration